2008
DOI: 10.4049/jimmunol.180.10.6997
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inflammatory Bowel Disease in Long-Evans Cinnamon Rats Based on CD4+CD25+Foxp3+ Regulatory T Cell Dysfunction

Abstract: A mutant strain with defective thymic selection of the Long-Evans Cinnamon (LEC) rat was found to spontaneously develop inflammatory bowel disease (IBD)-like colitis. The secretion of Th1-type cytokines including IFN-γ and IL-2 from T cells of mesenteric lymph node cells (MLNs) and lamina propria mononuclear cells, but not spleen cells, in LEC rats was significantly increased more than that of the control Long-Evans Agouti rats through up-regulated expression of T-bet and phosphorylation of STAT-1 leading to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…It is possible that ligand availability may be of pivotal importance under such conditions. In a previous study, TL1A-Ig augmented TCR-mediated proliferation of Foxp3 + Tregs, while at the same time, inhibited their suppressive capacity (48). Nevertheless, suppressive function was fully established in ex vivo Tregs upon removal of TL1A from the culture conditions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is possible that ligand availability may be of pivotal importance under such conditions. In a previous study, TL1A-Ig augmented TCR-mediated proliferation of Foxp3 + Tregs, while at the same time, inhibited their suppressive capacity (48). Nevertheless, suppressive function was fully established in ex vivo Tregs upon removal of TL1A from the culture conditions.…”
Section: Discussionmentioning
confidence: 89%
“…These opposite results may be explained by the dichotomous role of TL1A /DR3 in acute versus chronic inflammatory conditions. Nevertheless, an imbalance between Tregs and Th17 cells has been reported in both IBD and experimental colitis (48, 49). …”
Section: Discussionmentioning
confidence: 99%
“…CD4+Foxp3+Treg cells play a critical role in the maintenance of self tolerance, control of autoimmune diseases, transplant rejection and have also been documented to offer a therapeutic option in severe inflammatory colitis [5,8,[17][18][19][20]. Therefore, therapeutic agents that are capable of enhancing the number and activity of this T-cell subset are highly desirable.…”
Section: Discussionmentioning
confidence: 98%
“…Treg are able to suppress, via different mechanisms, many aspects of the immune responses [31]. They have been indicated to modulate the severity of inflammatory colitis [32][33][34][35][36]. Furthermore, in commensal bacteria-colonized mice it has been shown that particularly the IL-10 production by Treg cells plays a critical role in maintaining intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 98%